TEKNIK IODISASI GARAM MENGGUNAKAN MIXER KONTINYU BERMOTOR BENSIN - Prayitno Prayitno; Hadi Priyo S.; Harjono Harjono (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2015)
The availability of iodized salt in the community is needed in order to avoid disease GKY (Disorders Less Iodine). On the other hand, some salt producers are still facing some difficulties in producing air-iodized salt berstandart SNI caused by several factors, among others: the lack of proper iodized engineering, procurement difficulties and lack of law enforcement iodine to salt producers of non-iodium.Kegiatan IbM This aims to provide pengetahaun and skills for SMEs salt producers in producing air-iodized salt is good and right. Implementation of activities begins with the survey locations IbM, coordination meetings, iodine management training, technical training iodized salt, mixer equipment grants and consulting / mentoring. IbM activity results showed that the knowledge and skills of participants in producing air-iodized salt has increased as evidenced by the presence of air-iodized salt products resulting from these activities have met the standard IbM SNINo. 01-3556 years 1994yaitu iodine content in salt at 30 ppm - 80 ppm.